Confirmed viral meningitis with normal CSF findings. (17th July 2014) - Dawood, Naghum; Desjobert, Edouard; Lumley, Janine; Webster, Daniel; Jacobs, Michael
Abstract : An 18-year-old woman presented with a progressively worsening headache, photophobia feverishness and vomiting. Three weeks previously she had returned to the UK from a trip to Peru. At presentation, she had clinical signs of meningism. On admission, blood tests showed a mild lymphopenia, with a normal C reactive protein and white cell count. Chest X-ray and CT of the head were normal. Cerebrospinal fluid (CSF) microscopy was normal. CSF protein and glucose were in the normal range. MRI of the head and cerebral angiography were also normal. Subsequent molecular testing of CSF detected enterovirus RNA by reverse transcriptase PCR. The patient's clinical syndrome correlated with her virological diagnosis and no other cause of her symptoms was found. Her symptoms were self-limiting and improved with supportive management. This case illustrates an important example of viral central nervous system infection presenting clinically as meningitis but with normal CSF microscopy.